No place I'd rather be - Lamb, Cathy (Kensington Books, 2017)
Two years ago, Olivia Martindale left behind her Montana hometown and her husband, Jace, certain it was the best decision for both of them. Back temporarily to protect her almost-adopted daughters from their biological mother, she discovers an old, handwritten cookbook in the attic. Its pages are stained and torn, their edges scorched by flame. Some have been smeared by water . . . or tears. The recipes are written in different hands and in different languages. In between the pages are intriguing mementos, including a feather, a pressed rose, a charm, and unfamiliar photographs. Hoping the recipes will offer a window into her grandmother's closely guarded past, Olivia decides to make each dish, along with their favorite family cake recipes, and records her attempts. The result, like much of her life to date, involves a parade of near-disasters and chaotic appearances by her doctor mother, her blunt grandma, her short-tempered sister, and Olivia's two hilarious daughters. The project is messy, real--and an unintended hit with viewers. Even more surprising is the family history Olivia is uncovering, and her own reemerging ties to Montana, and to Jace.